Significance of agricultural residues in sustainable biofuel development - Mohammed, Nurudeen Ishola; Kabbashi, Nassereldeen Ahmed; Alade, Abass Olanrewaju (IntechOpen, 2018)
Bioenergy resources are considered clean and are an integral part of eforts to address the menace of climatic, economic, environmental, and social security challenges consequential from the utilization of fossil fuel, which is currently the main energy source. Bioenergy and biofuel utilizing biomass such as bioreinery, plant materials and manure, and waste resources for application as renewable fuels for transportation and for power generation can ensure a sustainable, low-carbon alternative to fossil fuels. Bioenergy is among the major plan to strategically phase out electricity generation from coal as well a comprehensive climate plan through carbon capture and other measures. Biomass selection sustainably has been advocated over time and reaction pathways are the other area of intensiied efort for an economical and environmentally synthesized process. Besides, the use of agricultural residues and manure to produce bioenergy ofers a signiicant opportunity for local and regional economies. In this chapter, various agricultural biomass residues which are an important energy resource are presented and the several studies where they have been explored in various locations of the world considering different approaches had been presented. Crop residues, in particular, are one of the largest biomass resources globally and the best options for use to produce bioenergy depending on local factors, including the type and scale of resources in each location are therein enumerated. It is observed that agricultural residues are an important resource for future biofuel and bioenergy generation sustainably.